From Bait al-Hikmah to Digital Platforms: Continuities in Islamic Knowledge Systems - Rahman, Gohar (Sinergi International Journal of Islamic Studies, 2024)
This study presents a comprehensive narrative review of the enduring contributions of Islamic civilization, focusing on intellectual innovation, institutional development, cultural expression, and global influence. The review aims to synthesize literature across disciplines to understand how Islamic heritage continues to shape modern science, governance, education, and intercultural exchange. Methodologically, the review employed purposive literature selection from databases such as Scopus and Google Scholar using key terms like "Islamic Civilization," "Islamic History," and "Muslim Institutions." Inclusion criteria focused on studies offering historical insight, critical analysis, and contemporary relevance. The findings demonstrate that Islamic civilization has profoundly influenced modern scientific thought, educational systems, and administrative models. Institutions like Bait al-Hikmah and Al-Azhar played critical roles in knowledge production and dissemination. The review also identifies the adverse impacts of colonialism, which disrupted traditional Islamic structures, and explores the resurgence of Islamic intellectualism through digital tools and interdisciplinary approaches. Cultural and educational policies in Muslim-majority nations increasingly reflect efforts to reconcile modern governance with Islamic values. This synthesis confirms that Islamic civilization provides foundational frameworks for addressing current global challenges. Emphasizing the revival of traditional knowledge systems and inclusive governance offers pathways to sustainable development and intercultural harmony. The study calls for integrative policy reforms and continued research on digital knowledge dissemination and postcolonial Islamic thought.